2022
DOI: 10.1002/qre.3166
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven maintenance planning and scheduling based on predicted railway track condition

Abstract: Timely planning and scheduling of railway infrastructure maintenance interventions are crucial for increased safety, improved availability, and reduced cost. We propose a data‐driven decision‐support framework integrating track condition predictions with tactical maintenance planning and operational scheduling. The framework acknowledges prediction uncertainties by using a Wiener process‐based prediction model at the tactical level. We also develop planning and scheduling algorithms at the operational level. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The uncertainty of the distribution of the time between failures (TBF) [34] is addressed by [35], who uses a Bayesian approach to estimate the strength of the population of replacement parts, and by [36], who considers the asset's age to update the failure rate of parts. Some PM approaches also consider the health state of components by performing periodic inspections [37] or by using prediction models, such as the Wiener process model [38]. Other studies, such as [39][40][41][42], focused on optimizing PM actions of repairable systems by considering imperfect maintenance actions.…”
Section: Related Workmentioning
confidence: 99%
“…The uncertainty of the distribution of the time between failures (TBF) [34] is addressed by [35], who uses a Bayesian approach to estimate the strength of the population of replacement parts, and by [36], who considers the asset's age to update the failure rate of parts. Some PM approaches also consider the health state of components by performing periodic inspections [37] or by using prediction models, such as the Wiener process model [38]. Other studies, such as [39][40][41][42], focused on optimizing PM actions of repairable systems by considering imperfect maintenance actions.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, CBM is typically applied to systems whose degradation states are available. CBM has been increasingly adopted in various fields, including railway, 14 subsea tree systems, 15 and wind turbines 16 . Studies have shown that CBM can effectively improve system reliability by utilizing the condition information for maintenance decision making 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Planned maintenance and unplanned maintenance are two ways of maintenance. [7][8][9] The former is known as preventive maintenance 10 while the latter is called corrective maintenance. 11,12 For a set of equipment, some of the subsystems require scheduled maintenance according to the maintenance manual from manufacturers.…”
Section: Introductionmentioning
confidence: 99%